2004
DOI: 10.1111/j.1365-2958.2004.04401.x
|View full text |Cite
|
Sign up to set email alerts
|

PMT family of Candida albicans: five protein mannosyltransferase isoforms affect growth, morphogenesis and antifungal resistance

Abstract: SummaryProtein O -mannosyltransferases (Pmt proteins) initiate O-mannosylation of secretory proteins. The PMT gene family of the human fungal pathogen Candida albicans consists of PMT1 and PMT6 , as well as three additional PMT genes encoding Pmt2, Pmt4 and Pmt5 isoforms described here. Both PMT2 alleles could not be deleted and growth of conditional strains, containing PMT2 controlled by the MET3-or tetOScHOP1-promoters, was blocked in non-permissive conditions, indicating that PMT2 is essential for growth. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
0
12

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(248 citation statements)
references
References 49 publications
13
223
0
12
Order By: Relevance
“…The requirement of pmt2 was confirmed by spore analysis of the diploid strain FBD11 Dpmt2/pmt2 (see Supplemental Figure 3 online). Our results concur with those previously obtained for members of the PMT2 subfamily in S. cerevisiae, C. albicans, and S. pombe (Gentzsch and Tanner, 1996;Prill et al, 2005;Willer et al, 2005) and thus reaffirm the requirement of the PMT2 subfamily for fungal viability.…”
Section: Pmt4 Is Required For Virulence On Maizesupporting
confidence: 82%
See 2 more Smart Citations
“…The requirement of pmt2 was confirmed by spore analysis of the diploid strain FBD11 Dpmt2/pmt2 (see Supplemental Figure 3 online). Our results concur with those previously obtained for members of the PMT2 subfamily in S. cerevisiae, C. albicans, and S. pombe (Gentzsch and Tanner, 1996;Prill et al, 2005;Willer et al, 2005) and thus reaffirm the requirement of the PMT2 subfamily for fungal viability.…”
Section: Pmt4 Is Required For Virulence On Maizesupporting
confidence: 82%
“…The loss of PMTs from S. cerevisiae, S. pombe, and C. albicans causes several defects, such as abnormal morphology, cellular aggregation, alterations in polar growth, and hypersensitivity to antifungal drugs, among others (Proszynski et al, 2004;Prill et al, 2005;Willer et al, 2005). To determine the effects of the deletion of pmt4 on U. maydis biology, we performed an in-depth analysis of Dpmt4, looking at the different phases of the U. maydis life cycle.…”
Section: Pmt4 Is Required Only For the Pathogenic Phase Of The U Maymentioning
confidence: 99%
See 1 more Smart Citation
“…Those studied include members of the PMT and MNT gene families, all of which act in O-glycosylation, and the studies have demonstrated the importance of O-glycans in virulence (19,(21)(22)(23)(24). Also, Mnn9p is involved in extension of the N-linked glycan outer chain and hence is required for normal cell wall composition (25).…”
mentioning
confidence: 99%
“…The pmt1 mutant, defective in the first steps of the O-glycosylation and partially responsible for Hwp1 glycosylation, 75,76 shows also a decrease in b-M epitopes observed in fraction 1 (100 C), 3 (NaOH) and 4 (zymolyase) and a shift in mannansḿ olecular weight. Interestingly, cells defective in either OCH1 or PMT1 constitutively display an increased Cek1 activation, 49,77 supporting therefore the idea that the Cek1-mediated pathway is essential for cell wall remodeling in C. albicans.…”
Section: Discussionmentioning
confidence: 99%